Luminescent, Oxygen‐Supplying, Hemoglobin‐Linked Conjugated Polymer Nanoparticles for Photodynamic Therapy. (27th June 2019) - Jiang, Linye; Bai, Haotian; Liu, Libing; Lv, Fengting; Ren, Xueqin; Wang, Shu
Abstract: Photodynamic therapy (PDT) is a promising method for cancer treatment. Two parameters that influence the efficacy of PDT are the light source and oxygen supply. Herein, we prepared a system for PDT using hemoglobin (Hb)‐linked conjugated polymer nanoparticles (CPNs), which can luminesce and supply oxygen. Hb catalyzes the activation of luminol, the conjugated polymer poly[2‐methoxy‐5‐(2‐ethylhexyloxy)‐1, 4‐phenylenevinylene] (MEH–PPV) nanoparticles can absorb the chemiluminescence of luminol through chemiluminescence resonance energy transfer (CRET) and then sensitize the oxygen supplied by Hb to produce reactive oxygen species that kill cancer cells. This system could be used for the controlled release of an anticancer prodrug. The system does not need an external light source and circumvents the insufficient level molecular oxygen under hypoxia. This work provides a proof‐of‐concept to explore smart and multifunctional nanoplatforms for phototherapy. Abstract : Kombinierte Wirkung : Ein neues System für die photodynamische Therapie (PDT) nutzt Hämoglobin‐verknüpfte konjugierte Polymernanopartikel, die lumineszieren und Sauerstoff liefern können. Es erfordert keine externe Lichtquelle und umgeht das Problem niedriger Sauerstoffspiegel in hypoxischem Gewebe. Es lässt sich zur kontrollierten Freisetzung eines Antikrebs‐Prodrugs nutzen und kombiniert damit PDT und Chemotherapie.